The Effect of Improved Sanitation on Linear Growth Amongst Children Living in Developing Countries: a Systematic Review - Chavura, Elton; Singini, Wales; Chidya, Russel; Mbakaya, Balwani Chingatichifwe (European Scientific Journal, ESJ, 2022)
Constant exposure to poor sanitation contribute to the environmental enteric dysfunction-a disorder that is frequently implicated as a cause of linear growth failure. We aimed to evaluate the efficacy of water, sanitation, and hygiene (WaSH) interventions on linear growth amongst children aged 0-24 months. We reviewed fourteen studies retrieved from AMED, CINAHL, DOAJ, PubMed, PsycINFO, Google Scholar, and EMBASE databases following guidelines developed by PROSPERO and COCHRANE. The screening process was summarized using a PRISMA flow diagram, and the methodologies were critically appraised by a Mixed Method Appraisal Tool. No difference was seen in mean height for age Z-score (0.01, 95% CI-0.16 to 0.18) between children who received WaSH interventions and those who did not. Only 5 studies reported a significant association between WaSH and child linear growth (P < 0.001). All combination intervention studies include in this review did not establish any significant benefit of WaSH and nutrition integration. Although robust sanitation coverage could be an important component amongst proven interventions to stimulate linear growth, stunted growth is embedded within myriad determinants beyond improved sanitation. More research is needed to quantify the complementary effect of WaSH and nutrition co-programming. This systematic review was registered in the PROSPERO database with registration number CRD42022322462.